Pengaruh Pola Asuh Orang Tua Terhadap Hasil Belajar Matematika Materi Aritmetika Sosial - Nahlika Purnamasari Nahlika; Novia Dwi Rahmawati (Cartesian: Jurnal Pendidikan Matematika, 2022)
The study aims to describe the parenting-pattern types applied by parents to their children and the effects of parenting patterns and learning outcomes of social arithmetic material. There are three types of parenting patterns they are democratic parenting, authoritarian parenting, and permissive parenting. From those types of parenting patterns, there will be one type that frequently happens and effects the learning outcomes of social arithmetic materal. The sample in this study use a saturated sample technique. Exposfacto anlyis is the type of research using quantitative methods taken from parental questionnaires and student test results. The instrument uses a parenting-style questionnaire and the result of students’mathematic tests for social arithmetic. The parental-questionnaires results and data on student test results correlated into three groups. The first group is 32 student with democratic parenting patterns they are 11 students with high scores, 15 students with moderate scorse, and six students with low scorse. The secpnd group is 12 students with authoritarian parenting-pattern they are two students with high scores, seven student with medium scores, and three low-scoring students. The last group is 20 students with permissive parenting with low overall scores.